Learning Lessons from Derna Dam Failures - Essam Saeid; Khalifa Eldursi; Taoufik Al Trabelci (Journal of Pure & Applied Sciences, 2025)
The dams in Libya have been built primarily for flood control, as seen with the Wadi Darna, Wadi Mejenin, and Wadi Qattarah Dams, as well as for supplying water to agricultural regions, including the Wadi Mejenin, Wadi Kaam, and Wadi Qattarah Dams. However, the effectiveness of these structures in managing floods and providing agricultural water has been inadequate. A recent example of this is the devastating dam failures at Wadi Derna, when the dams did not protect the city but instead the flood was made worse. Nevertheless, the destructive "Storm Daniel" event that struck northeastern Libya recently exceeded even the rainfall's dam design capability. Additionally, the dams' long-term flows and rainfall should be re-evaluated, and the size of the spillway and gates should be confirmed to determine whether the structures could sustain more severe floods like Daniel. The failure of the Derna and Abu Mansour dams offers significant insights for enhancing dam safety in Libya, particularly concerning the nine large dams. It is essential to assess all Libyan dams regarding their design, safety measures, and structural integrity to avert similar catastrophic incidents both in Libya and worldwide. It is essential to establish early warning systems to mitigate the impact of natural disasters. Creating flood hazard and risk maps in areas susceptible to flooding, particularly in seasonal wadis, which will serve as a foundation for developing future flood risk management strategies.